US land sector mitigation investments and emissions implications - Alice Favero; Christopher M. Wade; Yongxia Cai; Sara B. Ohrel; Justin Baker; Jared Creason; Shaun Ragnauth; Gregory Latta; Bruce A. McCarl (Nature Communications)
Abstract The land sector is anticipated to play an important role in achieving U.S. GHG emissions targets by reducing emissions and increasing sequestration from the atmosphere. This study assesses how much different levels of investment could stimulate land-based mitigation activities in the U.S. By applying a dynamic economic model of the land use sectors, with representation of 26 forestry and agricultural mitigation strategies across 11 U.S. regions, the study shows that annual investments of $2.4 billion could deliver abatement of around 80 MtCO2e annually. Under an optimal allocation of investments, the forestry sector and the Corn Belt are projected to receive the largest share of funds. Restricting land-based activities eligible for funds significantly reduces overall potential mitigation. For instance, if $24 billion investments are allocated only to agricultural activities, mitigation declines by 48% to 54 MtCO2e/yr over the next ten years. Finally, the level of abatement from each policy depends on the timing of implementation as the lowest cost mitigation actions are generally taken by the policy implemented first.